Determining minimum wages in China: Do economic factors dominate? - Christian Dreger; Reinhold Kosfeld; Yanqun Zhang (European Regional Science Association (ERSA), 2016)
Minimum wages may be an important instrument to reduce income inequality in a society and to promote socially inclusive economic growth. While higher minimum wages can support the Chinese transformation towards consumption driven growth, they can worsen the price competitiveness in export markets. As they differ throughout the country, this paper investigates their determinants at the regional level. In addition to a broad set of economic determinants, such as per capita income and consumption, consumer prices, unemployment and industrial structures, spatial effects are taken into account. They might arise for different reasons, including competition of local policymakers. The results show that the impact of economic variables declines, once spatial spillovers are considered. Although the minimum wage regulation pursues the relevance of economic factors in the determination of the appropriate levels, the actual development is largely driven by regional dependencies. As minimum wage standards set by local officials do not fully reflect the regional economic development, further reforms should be on the agenda.
Keywords: J30; R23; C23; 330; Chinese transformation; minimum wages; spatial effects